The Influence of Product Quality and Promotion on Consumer Purchase Decisions - Sulastri, R. Ela (Almana : Jurnal Manajemen dan Bisnis, 2023)
The research entitled The Influence of Product Quality and Promotion on Purchasing Decisions is a study of how big the influence of the quality of the products produced by the company and the promotional activities carried out to support marketing, resulting in purchasing decisions made by consumers. This research uses a descriptive and verification research design, with quantitative testing research methods. Descriptive analysis in this research uses continuum line analysis and verification analysis uses path analysis. The results of the analysis show that the quality of the products produced by the company is in the moderately improved category, this is supported by promotional activities carried out by the company which are considered quite good by respondents. Judging from the relationship and the magnitude of the influence between the variables studied, it shows that the quality of the product and promotions, both simultaneously and partially, have a positive relationship and have a significant influence on consumer purchasing decisions. Of the two variables studied, product quality has a greater influence than promotion on consumer purchasing decisions.